Pengaruh Buerger Allen Exercise Terhadap Nilai Ankle Brachial Index (Abi) pada Pasien Diabetes Mellitus Tipe 2 di Wilayah Kerja Puskesmas Lingsar - Erdiana, Baiq Iga Dwi (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Diabetes Mellitus (DM) type 2 tends to have Ankle Brachial Index (ABI) values lower than normal ranges due to lack of physical exercise and uncontrolled hyperglycemia conditions. DM management begins with applying a healthy lifestyle along with pharmacological and non- pharmacological interventions, one of which is physical activity such as Buerger Allen Exercise. To determine the effect of Buerger Allen Exercise on the value of Ankle Brachial Index (ABI) in patients with type 2 Diabetes Mellitus. Pre-Experimental research design with One Group Pretest- Posttest approach. The population is all Diabetes Mellitus patients who are in the Lingsar Health Center Working Area as many as 447 populations. Sampling using purposive sampling as many as 82. Data were collected using questionnaires and analyzed using the Wilcoxon Test. Buerger Allen Exercise can increase Ankle Brachial Index (ABI) values in patients with type 2 diabetes mellitus. As an alternative home treatment by doing buerger allen exercise to improve and improve blood circulation in the leg area